Synthesis, characterization, and electrochemical and electrical properties of novel mono and ball-type metallophthalocyanines with four 9,9-bis(4-hydroxyphenyl)fluorene - Agirtas, M. Salih; Altindal, Ahmet; Salih, Bekir; Saydam, Sinan; Bekaroglu, Ozer (Royal Soc Chemistry, 2011)
The new mono-nuclear 4-5 and ball-type homo-dinuclear 6 phthalocyanines have been synthesized from the corresponding phthalodinitrile derivative 3. The synthesized compounds have been characterized by elemental analysis, UV-vis, IR, H-1-NMR and MALDI-TOF-mass spectroscopies. The redox behaviours of the complexes were identified by cyclic voltammetry and square wave voltammetry. The temperature dependence of the electronic properties of compounds and adsorption of SO2 on thin film of 6 were investigated by conductivity measurements using an interdigital transducer structure on glass substrate. Dc conductivity, measured between 300-475 K, is thermally activated with the activation energy ranging between 0.67 and 0.90 eV. The ac conductivity is found to vary with frequency, omega, as omega(s) in which the frequency exponent s decreases with temperature suggesting a hopping conduction mechanism for all compounds. The SO2 sensing result showed that the spin coated film of 6 exhibits very good SO2 sensing properties, fast response and recovery rate, high sensitivity and good repeatability.
Keywords: Gas-Sensing Properties; Electrochromic Properties; Stabilized Zirconia; Thin-Films; Phthalocyanine; Sensor; Copper; So2; No2; Spectroelectrochemistry